English The origin and development of Sufism in Bengal and Assam in India - Khan, Nasir R (http://jagadalimussirry.com/, 2021)
Sufism refers to the mystical dimension of Islam, which, moving away from its rigid doctrinal form, speaks of self-realization, love, submission, and intense personal devotion as being the path to reach God. This paper attempts to understand Sufism and its essential principles, proceeding to trace its establishment and evolution in the Indian subcontinent, with a special focus on Bengal and Assam. The paper discusses the development of Sufism in the regions of Bengal and Assam by situating it in its precise historical and cultural context, exploring at length its interactions with the Bhakti movement and Buddhist Sahajiya tantrism, its impact on the folk art, culture and literature of the regions, and its role in shaping the socio-political climate of the regions over the ages. Lastly, the paper attempts to comment upon how Sufism, with its inherent variations and contradictions, survives in these regions today, and the significance that it holds for the people in contemporary times. In doing so, the paper attempts to understand whether Sufism and its ideals can become useful in promulgating a culture of peace and tolerance in an increasingly polarized and divided society.